2018
DOI: 10.1002/jbm.a.36461
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of stem cells from apical papilla into neural lineage using graphene dispersion and single walled carbon nanotubes

Abstract: Stem cell-based therapies are considered a promising treatment modality for many medical conditions. Several types of stem cells with variable differentiation potentials have been isolated from dental tissues, among them stem cells from apical papilla (SCAP). In parallel, new classes of biocompatible nanomaterials have also been developed, including graphene and carbon nanotube-based materials. The aim of the study was to assess whether graphene dispersion (GD) and water-soluble single walled carbon nanotubes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…. It has been demonstrated that CNTs can improve neurons responsiveness through creating tight physical interactions with cell membranes and stimulate the formation of active synaptic contacts between cells in culture …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…. It has been demonstrated that CNTs can improve neurons responsiveness through creating tight physical interactions with cell membranes and stimulate the formation of active synaptic contacts between cells in culture …”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that CNTs can improve neurons responsiveness through creating tight physical interactions with cell membranes and stimulate the formation of active synaptic contacts between cells in culture. [30][31][32] Fiber diameter is a very important feature of scaffolds that plays an active role in cell attachment and differentiation. It has been shown that aligned nanofibers with smaller diameters can promote neurite outgrowth compared with random nanofibers.…”
Section: Discussionmentioning
confidence: 99%
“…Such a nano-platform can be potentially utilized for the promoting neurite outgrowth and cell differentiation in the close perspective. In another work, the single-walled CNTs have been used to enhance neural differentiation of stem cells from apical papilla [148].…”
Section: Carbon Nanotubes and Stem Cellsmentioning
confidence: 99%
“…Recent studies have demonstrated the characteristics and capacity for multilineage differentiation of hSCAPs (26). Among the various dental-origin stem cell populations, hSCAPs exhibited superior pro ling, including multipotential differentiation, secretion of neurotrophic factors, and neurite outgrowth stimulation (27).…”
Section: Discussionmentioning
confidence: 99%